The effect of mineral transportation towards air quality index - Siti Nabila, Adrizal (2019)
This research aims to determine the correlation of mineral transportation and air quality index in Kuantan areas. The effect of environmental problems derived by mineral mining activities towards the local health was also investigated. The area chosen was categorized as mixed development area with industrial area and residential area are near to each other next to major road to/from Kuantan Port. The gas and dust productions within the area were monitored to determine the concentration of nitrogen dioxide (NO2), sulphur dioxide (SO2) and particulate matter 10 (PM10). Traffic volume counting was conducted at the exact time and location as the gas and dust productions were collected. The data was collected on three consecutive weekdays which were Tuesday, Wednesday and Thursday from 9AM to 6PM for two weeks. The correlation between mineral vehicles and air pollutant concentration were analysed and calculated by using linear regression and correlation. The results show that there is no significant correlation between air pollutant concentration and number of all vehicles and mineral vehicles class. However, there is a moderate correlation between the concentration of PM10 and number of mineral vehicles. The concentration of PM10 and the number of all vehicles and mineral vehicles class produced strong positive correlation coefficient. It shows that the concentration of PM10 is highly caused by number of heavy vehicles travelling on those areas.